Effects of Virtual Reality Technology in Disaster News Coverage Based on MAIN Model - Yan, Lihan; Jin, Xin; Zhang, Yundi (HCI International 2022 Posters, Communications in Computer and Information Science, 2022)
Using data of a between-group experiment (N = 40), this study examines the effects of virtual reality (VR) disaster news by comparing it with that of non-VR (traditional text news) disaster news on audiences from aspects of knowledge gain and risk perception based on the MAIN model. Results of ANOVA and structural equation modeling analysis revealed that audiences exposed to VR news coverage gain less knowledge about the disaster but perceive a higher degree of risk through the mediating effect of presence compared to those exposed to text news coverage. Therefore, this study concluded that VR is not effective and positive for making the public aware of facts of news but is suitable for improving risk awareness. Fig. 1. Theoretical Framework partially based on MAIN model Fig. 2. Structural equation modeling analysis framework Table 1. Result of ANOVA including heuristics, knowledge gain, and risk perception Table 2. Result of path analysis for each variable